The Role of Azure Data Lake in Scalable and High-Performance Supply Chain Analytics - Srikanth Yerra, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Growing complexity in global supply chains demands high- performance, scalable data management capabilities. Azure Data Lake offers a cloud-based platform wherein organizations can store, process, and analyze vast volumes of structured and unstructured data in a cost-effective manner. This study discusses how Azure Data Lake elevates supply chain analytics through the convergence of big data technologies, AI, and ML models. It is a mixed-method study, with case studies and statistical analysis being used for performance improvement measurement in supply chain activities.The main findings indicate that companies utilizing Azure Data Lake experience enhanced real-time decision-making, improved demand forecasting, and reduced inefficiencies in operations. However, challenges such as data protection and system integration persist. The paper concludes with sugges- tions for further research and strategies for optimizing Azure Data Lake utilization in supply chain analytics.
Keywords: Azure Data Lake; Supply Chain Analytics; Big Data; Cloud Computing; AI in Logistics; Predictive Analytics; Data Management; Machine Learning; Scalability; High Performance Computing